Flooding with shallow water promotes the invasiveness of Mikania micrantha. Issue 16 (21st July 2019) - Yue, Maofeng; Yu, Hanxia; Li, Weihua; Yin, Aiguo; Cui, Ye; Tian, Xingshan
Abstract: The invasive ability of alien plants is not only affected by their biological characteristics but also by environmental factors. Therefore, investigating the relationship between plant growth and environmental factors is helpful for predicting the invasive potential of alien species. Mikania micrantha H.B.K. (a vine of Asteraceae) is one of the top 10 most invasive weeds worldwide and causes serious damage to agroforestry ecosystems. Water is an important environmental factor that affects plant growth; however, the relationship between water conditions and the rapid growth of M. micrantha is not clear. In this study, 162 M. micrantha population sizes were investigated in dry, wet and aquatic habitats in the Pearl River Delta region of Guangdong, China. In addition, the seed germination and seedling growth characteristics of M. micrantha were determined by submerging tests. The results showed that the population size of M. micrantha was the largest in aquatic habitats, and the soil moisture content was positively correlated to the population size in dry and wet habitats. Furthermore, M. micrantha seeds could germinate underwater and grow out of the water surface at a depth of 6 cm with a survival rate of 7.4%. Aquatic habitat promoted vine elongation, whereas dry habitats resulted in the reverse pattern. After 8 weeks of water treatments, the vine stem length was 2 and 3 times longer in the aquatic habitat than the wet and dry habitats, respectively. The total root length, root volume, and root tip number increased significantly in the aquatic habitat when compared to those in the wet habitat; however, these parameters exhibited the opposite pattern in the dry habitat. The results showed that flooding with shallow water is conducive to the invasiveness of M. micrantha, suggesting that water is the key determinant during the intrusion process of M. micrantha populations. Open Research Badges: This article has been awarded Open Data, Open Materials and Preregistered research design Badges. All materials and data are publicly accessible via the Open Science Framework athttps://osf.io/ksz2f/?viewonly=30b6fec21f0447edbdfc9cebe2b01065, https://osf.io/a5ymf/ andhttps://osf.io/ksz2fl?viewonly=cfcbfOfc829c402fb22deb3be801dffc Abstract : Aquatic habitat promoted vine elongation of M. micrantha. M. micrantha seeds could germinate underwater and grow out of the water surface at a depth of 6 cm with a survival rate of 7.4%. The population size of M. micrantha was the largest in wetlands with shallow water, and the soil moisture content was positively correlated to the size of the coverage area in dry lands and riverbanks.